Questionnaire for the evaluation of university inclusive education (CEEIU) - De La Herrán Gascón, Agustin; Paredes Labra, Joaquín; Monsalve Treskow, Daniela Valeska (Revista Complutense de Educación, 2016)
The article is based on the approach of inclusive education, understood as a factor of excellence and academic quality. Its aim is to describe the process of drafting the “Questionnaire for the evaluation of university inclusive education” (CEEIU). The instrument aims to know how managers, university professors and university students understand and what they think about inclusive education in their universities and faculties. The instrument is simultaneously valid for the three groups of participants. The study was conducted at the Technical University of Manabí (Ecuador). The methodology went through these phases: 1st) Study and literature review and first draft of the instrument. 2nd) Content validation by external and internal experts and pilotage. 3rd) Implementation of the instrument. 4th) Study of reliability and final version of the questionnaire. The results indicate that the CEEIU is valid, includes notable educational values and is reliable. The internal consistency coefficient Cronbach’s alpha was 0.834.